2021
DOI: 10.3389/fmicb.2020.599062
|View full text |Cite
|
Sign up to set email alerts
|

Butylated Hydroxytoluene Induced Resistance Against Botryosphaeria dothidea in Apple Fruit

Abstract: Apple ring rot caused by Botryosphaeria dothidea is an important disease in China, which leads to serious economic losses during storage. Plant activators are compounds that induce resistance against pathogen infection and are considered as a promising alternative strategy to traditional chemical treatment. In the present study, butylated hydroxytoluene (BHT), a potential plant activator, was evaluated for its induced resistance against B. dothidea in postharvest apple fruits. The physiological and molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…When fruits are exposed to stress conditions, the production of ROS increases causing oxidative damage of cells and deterioration of fruit quality. POD, CAT, and APX are antioxidant enzymes, playing an important role in the protection of plant cells from the deleterious effects of ROS (Luo et al ., 2015; Huang et al ., 2021). These enzymes are involved in the elimination of hydrogen peroxide that can be harmful to plant cells.…”
Section: Resultsmentioning
confidence: 99%
“…When fruits are exposed to stress conditions, the production of ROS increases causing oxidative damage of cells and deterioration of fruit quality. POD, CAT, and APX are antioxidant enzymes, playing an important role in the protection of plant cells from the deleterious effects of ROS (Luo et al ., 2015; Huang et al ., 2021). These enzymes are involved in the elimination of hydrogen peroxide that can be harmful to plant cells.…”
Section: Resultsmentioning
confidence: 99%
“…Various extracellular enzymes are secreted into the decayed tissue by the fungus to disassemble the cell wall of the fruit during colonization [ 30 ], causing the degradation of the cell wall polysaccharide and the increase in the soluble sugar contents [ 31 ]. Moreover, fungal colonization facilitates the breakdown of the vacuole of fruit [ 32 ], which causes the leakage of the stored fructose and glucose into to the apoplasmic space in the fruit cells [ 33 ]. Our results showed that fungus prefers to degrade or directly use sucrose as a carbon source during colonization, which caused a rapid decrease in the sucrose content in the decayed tissue.…”
Section: Resultsmentioning
confidence: 99%
“…italicum-induced oxidative damage. Reduction of firmness loss and electrolyte leakage following exogenous treatment of Botrytis cinerea-infected “Akihime” strawberry with linalool, Botryosphaeria dothidea-infected “Fuji” apple with benzothiadiazole, and A. alternata-infected “Zaosu” pear with l -lysine was reported, indicating that these PAAs support the maintenance of the cell wall structure and cell membrane integrity and in turn mediate antifungal resistance in harvested fruit.…”
Section: Discussionmentioning
confidence: 99%
“…34,42 We showed here that DEM treatment suppressed peel firmness loss and electrolyte leakage in P. italicum-infected fruit (Figure 1C,D), indicating that the treatment controlled CBM development by reducing P. italicum-induced oxidative damage. Reduction of firmness loss and electrolyte leakage following exogenous treatment of Botrytis cinerea-infected "Akihime" strawberry with linalool, 43 Botryosphaeria dothidea-infected "Fuji" apple with benzothiadiazole, 44 and A. alternata-infected "Zaosu" pear with L-lysine 27 was reported, indicating that these PAAs support the maintenance of the cell wall structure and cell membrane integrity and in turn mediate antifungal resistance in harvested fruit.…”
Section: Discussionmentioning
confidence: 99%